The Role of Artificial Intelligence in Enhancing Academic Performance among University Students - Daisy Mui Hung Kee; Min Zhe Tee; Tasnim Amani Abdul Razak; HaoJie Tang; Yii Thong Teng; Kartik Katoch; Vanshika Agrawal (AIBPM Publisher, 2026)
In recent year,Artificial Intelligence (AI) has become a crucial component in higher education, reshaping how students study, access information, and complete assignments.AI-powered tools, including chatbots, plagiarism detection software, and adaptive learning systems, enable more efficient, interactive, and personalised learning experiences. With increasing AI adoption in universities, understanding how these technologies affect students’ academic performance and learning behaviour is crucial. This study aims to examine the role of AI in enhancing academic performance among university students by focusing on perceived usefulness, ease of use, trust, risk, and learning engagement. Our findings indicate that Personalised Learning, Intelligent Feedback and AI-Driven Assessment Learning Analytics significantly and positively affect university students academic performance. Among these, Personalised Learning and AI-Driven Assessment Learning Analytics exerted the strongest influence on academic performance. These findings underscore the pivotal role of AI-driven tools in enhancing student behaviour and academic performance in higher education.